Use some applications on mobile phones supporting grade-12 students in self- studying mathematics - Trinh, Thi Phuong Thao (Đại học Quốc gia Hà Nội, 2020)
From 2019, the Ministry of Education and Training in Vietnam will launch a new general education program. The focus of this program is emphasized with contents of developing the core capacity for students, which are the general capacity (including self-control, autodidacticism, communications and co-operation, problem solving and creation) and special capacity, through different educational methods such as differentiated teaching, integrative teaching and activity-via teaching. In addition, mobile phones are becoming a vital part daily life of almost students and teachers in the era of the Industrial Revolution 4.0. With the support of mobile devices capable of accessing the Internet, the mobile learning method has been formed: M-learning. Based on the findings of the thesis which investigated some applications on mobile phones supporting grade-12 students in self-studying Mathematics, this paper presents a number of self-study solutions for students with the support of M-learning towards developing students’ self-learning ability